SEXUAL HEALTH AND AGING: LITERATURE REVIEW AND NOTES FOR SEX EDUCATION - Claudia Bortolozzi, Ana [UNESP]; Ramos Netto, Tatiana de Cassia [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
Life expectancy has increased in Brazil and ageing, as a biological and psychosocial phenomenon, is a phase of attention of professionals and researchers. Although there are prejudices about sexuality in aging, many elderly people have an active sexual life and are vulnerable to sexually transmitted infections. This documentary research conducted a literature review on sexual health and aging, selecting 68 articles for content analysis. The articles were found between 2001 and 2018, most of them in 2015 and in the areas of Nursing, Collective Health and Gerontology. The results were described in the categories: (A) Violence against elderly; (B) Diseases and physical problems in aging; (C) Sexual health and sexuality; (D) Experiences of elderly with HIV/AIDS. (E) HIV/AIDS and elderly: vulnerability and prevention. The need for sex education to decrease the level of vulnerability of older people to sexual health is concluded.
Keywords: Aging; Sexual Health; Sexual Education